Management and outcome of patients with atrial fibrillation during acute myocardial infarction: the GUSTO-III experience. Issue 4 (1st October 2002) - Wong, C-K; White, H D; Wilcox, R G; Criger, D A; Califf, R M; Topol, E J; Ohman, E M
Abstract : Objective: To investigate the use of antiarrhythmic agents and electrical cardioversion in the management of patients with atrial fibrillation complicating acute myocardial infarction, and their relation to 30 day and one year mortality. Design: Prospective study of 1138 patients with atrial fibrillation from the GUSTO-III trial. Interventions: Of the 1138 study patients, 317 (28%) received antiarrhythmic treatment, including class I antiarrhythmic agents (12%), sotalol (5%), and amiodarone (15%); electrical cardioversion was attempted in 116 (10%). Results: Sinus rhythm was restored in 72% of patients receiving class I antiarrhythmic agents, 67% of those receiving sotalol, 79% of those receiving amiodarone, and 64% of those having electrical cardioversion. After adjusting for baseline characteristics and complications occurring before the onset of atrial fibrillation, there was no difference among the treatment groups in the incidence of sinus rhythm at the time of discharge or before deterioration to hospital death. However, the use of class I antiarrhythmic drugs or sotalol was associated with a lower unadjusted 30 day and one year mortality. After adjustment for baseline factors and pre-atrial fibrillation complications, the odds ratios for 30 day and one year mortality were 0.42 (95% confidence interval (CI) 0.19 to 0.89) and 0.58 (95% CI 0.33 to 1.04) with class I agents, and 0.31 (95% CI 0.07 to 1.32) and 0.31 (95% CI 0.09 to 1.02) with sotalol. In contrast, there was no association between the use of amiodarone or electrical cardioversion and 30 day or one year mortality. Conclusions: There was a strong trend towards lower mortality associated with the use of class I antiarrhythmic agents or sotalol in managing patients with atrial fibrillation after acute myocardial infarction. Randomised trials are indicated.